Influence of Biphasic Stimulation on Olfactory Ensheathing Cells for Neuroprosthetic Devices - Hassarati, Rachelle T.; Foster, L. John R.; Green, Rylie A. (Frontiers in Neuroscience, 2016)
The recent success of olfactory ensheathing cell (OEC) assisted regeneration of injured spinal cord has seen a rising interest in the use of these cells in tissue-engineered systems. Previously shown to support neural cell growth through glial scar tissue, OECs have the potential to assist neural network formation in living electrode systems to produce superior neuroprosthetic electrode surfaces. The following study sought to understand the influence of biphasic electrical stimulation (ES), inherent to bionic devices, on cell survival and function, with respect to conventional metallic and developmental conductive hydrogel (CH) coated electrodes. The CH utilised in this study was a biosynthetic hydrogel consisting of methacrylated poly(vinyl-alcohol) (PVA), heparin and gelatin through which poly(3,4-ethylenedioxythiophene) (PEDOT) was electropolymerised. OECs cultured on Pt and CH surfaces were subjected to biphasic ES. Image-based cytometry yielded little significant difference between the viability and cell cycle of OECs cultured on the stimulated and passive samples. The significantly lower voltages measured across the CH electrodes (147 ± 3 mV) compared to the Pt (317 ± 5 mV), had shown to influence a higher percentage of viable cells on CH (91 - 93 %) compared to Pt (78 - 81 %). To determine the functionality of these cells following electrical stimulation, OECs co-cultured with PC12 cells were found to support neural cell differentiation (an indirect measure of neurotrophic factor production) following ES.